Expansion of a versatile pathogen: Clostridioides difficile - Tereena Lucas; Brent Brown (Elsevier, 2024)
Clostridioides difficile is a gram positive and spore forming bacterium responsible for significant global morbidity and mortality. There is increasing incidence of C. difficile disease that constitutes a deviation from the traditionally understood toxin-mediated colonic disease. Comprehensive literature review has determined a conservative increase of over 600 cases of C. difficile extra-intestinal and small-intestinal disease detailed in >200 papers over the past 20 years. Chronic colonization with increased intestinal permeability that permits the translocation of toxins and metabolites may partially explain this expanded disease manifestation. Currently there is little evidence in support of a role for toxins however, and greater evidence to support the role of metabolites in extra-intestinal disease pathogenesis. Specifically, increased levels of p-cresol, p-cresyl sulfate, indoxyl sulfate and ammonia are associated with C. difficilecolonization. One important health consideration involves ongoing biotransformation of such metabolites, together with the overall metabolic load from all endogenous and exogenous sources, that can result in glutathione depletion. Chronic glutathione depletion in turn increases oxidative stress and is correlated with neurological compromise across all age groups, and a host of other conditions. Key factors supporting chronic colonization with C. difficile in susceptible hosts include widespread and indiscriminate use of antimicrobials, pharmaceuticals, pesticides, intensive agricultural practices, diet, food additives, and gastrointestinal disturbances. Appreciation of the role of the exposome in C. difficile disease expansion will further emphasize the importance of decreasing environmental contamination, antimicrobial resistance, inter-species transmission, and individual toxic metabolite burdens.